An estrogen-dependent four-gene micronet regulating social recognition: A study with oxytocin and estrogen receptor-α and -β knockout mice - Choleris, Elena (The National Academy of Sciences, 2003)
Estrogens control many physiological and behavioral processes, some of which are connected to reproduction. These include sexual and other social behaviors. Here we implicate four gene products in a micronet required for mammalian social recognition, through which an individual learns to recognize other individuals. Female mice whose genes for the neuropeptide oxytocin (OT) or the estrogen receptor (ER)-β or ER-α had been selectively “knocked out” were deficient specifically in social recognition and social anxiety. There was a remarkable parallelism among results from three separate gene knockouts. The data strongly suggest the involvement in social recognition of the four genes coding for ER-α, ER-β, OT, and the OT receptor. We thus propose here a four-gene micronet, which links hypothalamic and limbic forebrain neurons in the estrogen control over the OT regulation of social recognition. In our model, estrogens act on the OT system at two levels: through ER-β, they regulate the production of OT in the hypothalamic paraventricular nucleus, and through ER-α, they drive the transcription of the OT receptor in the amygdala. The proper operation of a social recognition mechanism allows for the expression of appropriate social behaviors, aggressive or affiliative.